Exploration of Indigenous Anaerobic Microbes From The Soil of Mount Ringgit, Situbondo: - - Nurul Avidhah Elhany; Ahmad Taufikur Rahman (BIOVALENTIA: Biological Research Journal, 2026)
Soil is an ecosystem containing various types of microbes with varying morphological and physiological properties. The number of each microbial group varies greatly, with some consisting of only a few individuals, while others number up to millions per gram of soil. The number of microbes influences the chemical and physical properties of the soil, as well as plant growth. By understanding the number and activity of microbes in a soil, it is possible to determine whether the soil is fertile or not, because a high microbial population indicates an adequate food/energy supply, appropriate temperature, sufficient water availability, and soil ecological conditions that support microbial growth. This study aimed to explore and isolate indigenous anaerobic microbes from the soil of Mount Ringgit, Situbondo, and identify their initial characteristics. This study employed a descriptive exploratory approach with laboratory experimental methods. Soil samples were collected using purposive sampling. The isolation process was carried out using a multilevel dilution technique followed by incubation under anaerobic conditions. The growing colonies were then purified and characterized macroscopically and microscopically. The results of the study showed that two distinct anaerobic bacterial isolates were obtained. Based on characterization, the isolates were identified as Clostridium sp. and Thiobacillus denitrificans. The presence of these two bacteria indicates that the soil of Mount Ringgit, Situbondo, has the potential for anaerobic microbial diversity, which plays a role in the decomposition of organic matter and the transformation of inorganic compounds.